Cheaper by the dozen eaudiobook - Gilbreth, Frank B. (Cheaper by the Dozen, 2003)
No growing pains have ever been more hilarious than those suffered loudly by the riotous Gilbreth clan. First, there are a dozen red-haired, freckle-faced kids to contend with. Then there's Dad, a famous efficiency expert who believes a family can be run just like a factory. And there's Mother, his partner in everything except discipline. How they all survive such escapades as forgetting Frank, Jr., in a roadside restaurant or going on a first date with Dad in the backseat or having their tonsils removed en masse will keep you in stitches. You can be sure they're not only cheaper, they're funnier by the dozen.